A new rotary ultrasonic motor using longitudinal vibration transducers. (21st May 2015) - Zhou, Xiangyu; Chen, Weishan; Liu, Junkao
To simplify the design process and improve the motor performance, a rotary ultrasonic motor with rotationally symmetrical structure has been designed, fabricated, and characterized. The stator consists of four connected sandwich-type transducers and eight driving feet. The rotor, a disk, and a disk-shaft are pressed on the two sides of the stator by a nut–spring system. To drive the rotor, two orthogonal longitudinal vibration modes of the stator should be excited. The operating principle of the rotary motor was analyzed by a mathematical model. By using finite element analysis, the feasibility of the operating principle was validated, and the optimal structure dimensions of stator were determined in order to improve the driving teeth motion. The overall dimensions of the prototype stator are 30 mm (width) × 30 mm (width) × 50 mm (length). Driven by alternating current signals with the driving frequency of 50.93 kHz and voltage 300 VP-P, the motor gave a maximal no-load speed of 157.9 r/min and a maximal output torque of 11.76 mN m.